Toward human-centric urban infrastructure: Text mining for social media data to identify the public perception of COVID-19 policy in transportation hubs. (January 2022) - Park, June Young; Mistur, Evan; Kim, Donghwan; Mo, Yunjeong; Hoefer, Richard
Highlights: The study proposed the human-centric facility management to investigate and incorporate the human perceptions of COVID-19 policy for healthy and safe airports. We identified 4 representative topics (Staff, Shop, Space, and Service) from 103, 428 social media reviews in 64 hub airports in the US using text mining techniques. Due to the behavioral changes required by COVID-19 policy, passengers began to identify Space and Service issues, where we can potentially improve the user experience in airports. The research framework can be used to discover the human perceptions of other urban infrastructures. Abstract: The COVID-19 pandemic has made transportation hubs vulnerable to public health risks. In response, policies using nonpharmaceutical interventions have been implemented, changing the way individuals interact within these facilities. However, the impact of building design and operation on policy efficacy is not fully discovered, making it critical to investigate how these policies are perceived and complied in different building spaces. Therefore, we investigate the spatial drivers of user perceptions and policy compliance in airports. Using text mining, we analyze 103, 428 Google Maps reviews of 64 major hub airports in the US to identify representative topics of passenger concerns in airports (i.e., Staff, Shop, Space, and Service). Our results show that passengers express having positive experiences with Staff and Shop, but neutral or negative experiences with Service and Space, which indicates how building design has impacted policy compliance and the vulnerability of health crises. Furthermore, we discuss the actual review comments with respect to 1) spatial design and planning, 2) gate assignment and operation, 3) airport service policy, and 4) building maintenance, which will construct the foundational knowledge to improve the resilience of transportation hubs to future health crises.